Design Of Switched Reluctance Motor Using Empirical Method - Abdullah, N; Kasrul, Abdul Karim; Mohd Luqman, Mohd Jamil; Md Nazri, Othman (UM Power Energy Dedicated Advanced Centre (UMPEDAC), 2014)
This paper presents a design and development of switched reluctance motor (SRM) for electric scooter using empirical method. The torque characteristic, inherent fault tolerance capabilities, simple and robust construction make this motor become more attractive for small electric vehicle application such as electric scooter. The switched reluctance motor is modeled using empirical ratio and established for a quick references in designing process. Later, the designed model is analyzed using ANSYS Maxwell finite elements software. In meeting the desired performances and to match with the design requirement, the SRM model has been analyzed using RMxprt tools for the preliminary parameters design process. Next, the model has been simulated in Maxwell two dimensional (Maxwell 2D) with standard external circuit for accurate verification. This modeling technique is expected to be able to predict the output performance of motor in term of speed, flux linkage characteristic, output torque and efficiency.